Linkages between Time to Reach Education Centers, Health Facility Centers, Poverty Status and Geography: A Multivariate Approach - Uprety, Pravat (Nepalese Journal of Statistics, 2019)
Background: The first, third and fourth goals of SDG are concerned with ending poverty in all its forms everywhere, ensure healthy lives and promote well-being for all at all ages and ensure inclusive and equitable quality education and promote lifelong learning opportunities for all, respectively. Nepal is committed to ensuring all children with access to free, compulsory, and good-quality basic and secondary education in Nepal. Objectives: This study aims to compare the average time to reach education centers and health facility centers by poverty status and ecological region. Materials and Methods: This study is based on NLSS 2011 data. In this study two major factors of access to facility namely education and health are considered. Four variables on access to education and three variables on access to health are used. Mean vectors, correlation matrices, and covariance matrices have been computed. The Multivariate Analysis of Variance is used to compare the mean vectors and to check the homogeneity of the variance-covariance matrix using Box's M test. Four tests namely Wilk's Lambda, Lawley- Hoteling trace, Pillai trace and Roy's largest root have been used to compare the mean vectors. Results: This study has shown that the average time to reach each nearest education center of poor households is higher than non-poor households in each ecological region. The average time to reach the primary school is lowest and highest to reach secondary school in each poverty status and ecological region. The average time to reach the nearest health post is lowest among different health facility centers in each poverty status and ecological region. The p-values of each Box's M and Pillai trace tests are less than 0.0001. Conclusion: The mean vectors of time to reach the nearest education center are significantly different between poor and non-poor households in each ecological region. The average time to reach the health facility centers is also significantly different in poor and non-poor households within each ecological region.